Unusual cause of intraoperative haemorrhage: a lesson for patient counselling. Issue 6 (9th June 2022) - Alghazawi, Laith Omar Khalaf; Holtermann Entwistle, Olivia; Fehervari, Matyas; Spalding, Duncan
Abstract : Hepatocellular carcinoma (HCC) is a well-known malignant neoplasm of the liver associated with spontaneous haemorrhage in 3%–15% of cases. This complication is life threatening and has a mortality rate of 33%–100%. Despite the frequency and severity of spontaneous haemorrhage, the importance of patient education about this complication has not been highlighted before. There is currently no information available on the NHS UK website, and no publications have addressed the effect of patient education. We present this case report describing a patient who developed classical symptoms of haemorrhage the day before her elective HCC resection, but was unaware of its importance, and thus did not seek medical attention. She was subsequently found to have a large volume haemoperitoneum, anaemia and a ruptured HCC intraoperatively. This case illustrates the significant importance of counselled regarding the symptoms and risk of spontaneous rupture of HCC to prompt early presentation to medical services.